2016
DOI: 10.2217/pgs-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Implementation of Prospective DPYD Genotyping in 5-Fluorouracil- or Capecitabine-Treated Patients

Abstract: Prospective DPYD screening can be implemented successfully in a real world clinical setting, is well accepted by physicians and results in low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Several gene/drug examples have been described for decades, 1 with various degrees of implementation across oncology institutions and practices. [42][43][44] We used a previously published method 19 to critically assess the vast number of germline pharmacogenomic studies about oncology drugs. It is noteworthy that the majority of drugs have had positive pharmacogenomic associations described about them (67 of the 125 drugs), with published associations for 12 drugs withstanding rigorous evidence standards required for clinical actionability.…”
Section: Discussionmentioning
confidence: 99%
“…Several gene/drug examples have been described for decades, 1 with various degrees of implementation across oncology institutions and practices. [42][43][44] We used a previously published method 19 to critically assess the vast number of germline pharmacogenomic studies about oncology drugs. It is noteworthy that the majority of drugs have had positive pharmacogenomic associations described about them (67 of the 125 drugs), with published associations for 12 drugs withstanding rigorous evidence standards required for clinical actionability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pharmacogenetics guidelines for the management of FL-based chemotherapy toxicity in colorectal cancer agree upon the clinical validity of DPYD*2A DPYD*13, c.2846A>T and c.1236G>A-HapB3, a pre-emptive genotyping to avoid severe and unpredictable adverse drug reactions, translating such recommendations in the clinical practice remains a matter of open debate [21,22]. Prospective evidences of increased FL safety and efficacy when applying a DPYD*2A-guided dose reduction was reported, which strongly justify a drug label update limited to the well-known DPYD*2A variant [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies with a DPYD-PGx/clinical monitoring combination, five out of eleven studies confirmed the importance of DPYD variants in predicting FP-related toxicity, although a too-short clinical monitoring was performed (only two treatment cycles) [21,23,29,31,39]. Two studies [24,34] analysed only DPYD*2A of the DPYD SNPs currently recommended.…”
Section: Systematic Reviewmentioning
confidence: 97%